CCDC25 suppresses clear cell renal cell carcinoma progression by LATS1/YAP-mediated regulation of the hippo pathway - Hongpei Tan; Jiahao Liu; Yanan Li; Ze Mi; Baiying Liu; Pengfei Rong (Cancer Cell International, 2024)
Abstract Background Clear cell renal cell carcinoma (ccRCC) is one of the most prevalent renal cancers, and the molecular mechanisms underlying its progression are still not fully understood. The expression of CCDC25, a notably underexpressed gene in many tumors, has been understudied in ccRCC. This research aims to explore the role of CCDC25 in ccRCC's clinical outcomes and uncover the molecular pathways influenced by it. Methods A multi-tiered approach was adopted involving bioinformatic analysis, tissue sample evaluation, in vitro and in vivo experiments. CCDC25 expression levels in tumor vs. normal tissues were quantified using Western blot and immunofluorescence studies. Cell proliferation and migration were analyzed using CCK8, EDU, Transwell assays, and wound healing assays. RNA sequencing was performed to elucidate the molecular pathways affected, followed by detailed protein–protein interaction studies and mouse xenograft models. Results CCDC25 was predominantly underexpressed in ccRCC tumors and associated with advanced clinical stages and poor prognosis. Overexpression of CCDC25 in renal cancer cell lines resulted in reduced proliferation and migration. RNA sequencing revealed significant alterations in the Hippo pathway. Overexpression of CCDC25 inhibited the expression of downstream Hippo pathway proteins ITGA3 and CCND1 and promoted YAP phosphorylation. Mechanistic studies showed that CCDC25 interacts with YAP and influences YAP phosphorylation through LATS1. In vivo, CCDC25 overexpression inhibited tumor growth and promoted apoptosis. Conclusion CCDC25 acts as a potential tumor suppressor in ccRCC by inhibiting cell proliferation and migration, potentially through regulating the Hippo signaling pathway. These findings highlight the potential of CCDC25 as a therapeutic target in ccRCC treatment. Graphical Abstract